Controlling Post-Operative Pain with Early Mobilization and Music Therapy - Muawanah, Kholisatul; Sulastri, Sulastri (Poltekkes Kemenkes Tanjung Karang, 2023)
Pain is the main complaint that is commonly experienced by patients undergoing surgery. The pain appears as a normal response after surgery with injury to the incision area. This study aimed to determine the effect of early mobilization and music therapy on pain intensity in postoperative patients. The quasi-experimental research design used a pre-test and post-test with a control design. The sample was 32 people, divided into experimental and control groups, each of which consisted of 16 respondents. The sampling technique uses the Accidental Sampling approach. The variable in the assessment is pain intensity as the dependent variable, while the independent variables are early mobilization and music therapy. Pain measurement was performed using the Numeric Rating Scale (NRS). The analysis used the Wilcoxon test to test pain intensity before and after treatment in the intervention and control groups while testing the difference in pain intensity between the intervention and control groups using the Mann-Whitney test. The Wilcoxon test results obtained a p-value of 0.000 (Î±